STUDIO FILM DI BANJARBARU - Moh. Habibullah; Nursyarif Agusniansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Films consist of audio and visual sequences that have the ability to influence the audience's emotions by conveying messages through visual images. Therefore, a film studio is needed that provides facilities for producing a film. In line with technological advances, this studio also has mini studio facilities which function as additional indoor shooting locations using digital effects. In accommodating these activities, the Film Studio in Banjarbaru will be designed by applying the functional architectural method with the Functional Space concept, namely that the design must pay attention to the main purpose of each room, so that every element in the studio building is well arranged for the needs of film production activities. The character of space in a film studio is divided into two concepts based on its main function, namely production and post-production space. The production room functions as a place for the production team to carry out filming activities, so a space design that is mutually supportive and sustainable is needed. Meanwhile, the character of the post-production room is designed to provide focus on the editing process so that a quality final film product is obtained.